Manajemen Kurikulum Pendidikan Islam di Pondok Pesantren Al-Husna Riau - Assilmi, Habib Hariansyah; Tanjung, Ellisa Fitri (At-Tadris: Journal of Islamic Education, 2024)
Curriculum management is a cooperative, comprehensive, systemic and systematic curriculum management system in order to realize the achievement of curriculum objectives. The implementation of curriculum management must develop in accordance with the context of school-based management (MBS) and the education unit level curriculum (KTSP). Success in the implementation of Islamic education institutions will depend heavily on the components of Islamic education curriculum management such as teaching and education staff management, school management, subject management, subject schedule management, financing management, and infrastructure management. These components are an integral part of efforts to achieve the goals of educational institutions, especially Islamic education based on Islamic boarding schools. The method used in this research is a qualitative method with a descriptive approach. The techniques used in collecting data were observation, in-depth interviews and documentation. Data analysis was carried out by categorizing and interpreting data in narrative form. Curriculum management in the national education system is a very complex process and involves various interrelated components in order to direct all forms of educational activities to achieve national education goals. Curriculum management procedures consist of curriculum planning, curriculum implementation, and curriculum evaluation.